Synchronous and Futuristic Views on the Application of Silver Nanoparticles: A Journey towards Green Synthesis. (4th April 2022) - Nagaprasad, N.; Chandralekha, D.; Karri, Veera Venkata Satyanarayana Reddy; Shanmugam, R.; Dwarampudi, L. Priyanka; Tesfaye, Jule Leta; Krishnaraj, R.
Abstract : Historically, silver has been recognized as a powerful antibacterial agent with a broad spectrum of functions, and it has been employed safely in healthcare for several years. It seems that the incorporation of silver into embedded medical devices may be advantageous when particular genetic features, including such antibacterial behavior, are needed for the device to function. According to current and prior bacterial studies, it appears that the toxicity against bacteria was significantly more significant than the toxicity against human cells. Silver nanoparticles are nanoparticles with sizes ranging between one and one hundred nanometers (nm) in size. When it comes to molecular diagnostics, therapies, and equipment that are employed in a wide range of medical procedures, silver nanoparticles have a number of unique qualities that make them very useful. The physical and chemical approaches are the two majority ways for the creation of silver nanoparticles. The challenge with chemical and physical approaches is that the synthesis is complicated and can result in harmful compounds being absorbed onto the surfaces of the materials. In order to address this, the biological technique offers a viable alternative solution. Bacteria, fungus, and plant extracts are the three principal biological systems concerned in this process. A complete overview of the mechanism of action, manufacture, and uses in the medical area, as well as the healthcare and ecological concerns that are believed to be produced by these nanoparticles, is provided in this paper. The emphasis is on the proper and effective synthesis of silver nanoparticles even while exploring their numerous promising utility and attempting to assess the current status in the debates over the toxicity concerns that these nanoparticles pose, as well as attempting to reflect the needs in the debates over the toxicity concerns that these nanoparticles pose.